The effectiveness of natural soil and kenaf fibre mixture in riverbank filtration system - Nur Ain Zatia, Zamri (2014)
Water is an essential resource that sustains life on earth. Clean and safe water supply is very demanding as the population are kept increasing as the years goes by. There are many methods to produce safe and clean water for daily purposes which might include a chemical reaction for the treatment. But most of the method involve a lot of procedures and definitely very costly. Recent study has found that riverbank filtration system is one of a new method that is naturally filtrate water at the river specifically without adding any chemicals. The soil properties might be different in each location so the standard water quality that needs to be achieved might be unsuccessful. The main objectives of this study are to identify the applicability of kenaf fibre and natural soil mixture as artificial barrier in riverbank filtration system and to determine the effectiveness of kenaf fibre and natural soil mixture in removing contaminants, organics and biological content. Riverbank filtration (RBF) systems are particularly well suited for providing better water quality than withdrawal directly from the surface water. Reliable RBF systems can remove microbial pathogens, organic contaminants, hormones, endocrine disruptors, turbidity, and other substances. The efficiency might vary from one location to another location because the efficiency of the system depends on the properties of the soil. So, modification is required in achieving reasonable treatment ability. In this study, natural soil from Chini Lake riverbank was considered and the effectiveness in improving the quality and appearance of water sample been investigated. New material which is kenaf fibre were used for this research where the effectiveness of the mixture of the natural soil and kenaf fibre were analysed to modify the soil. Several tests, namely adsorption test and filtration test was conducted in the laboratory to determine the effectiveness of both material as filtration medium. Result shows that the soil is clay soil with low plasticity. Parameter that been considered are Biochemical Oxygen Demand,Chemical Oxygen Demand, Turbidity, Total Suspended Solid and Total Dissolved Solid. Result had indicated that the mixture of natural soil and kenaf fibre are not effective enough as filtration medium to produce better water quality.